Motivation for Changing Jobs, Personal Background Characteristics and Perceived Opportunity - Dornstein, Miriam; Zoref, Uri (Relations industrielles / Industrial Relations, 1986)
A cross-organizational and cross-occupational sample of employees in the process of changing theirjobs was chosen for investigating the relationship between turnover and a variety of background characteristics and perceived opportunity. Following recent theoretical conceptualizations the investigation focused on: (1) the relationship between the background characteristics and satisfaction with various facets in the present job, attraction to various facets in the prospective job and number of perceived alternatives; (2) the relationship between the number of perceived alternatives and satisfaction with the present job and attraction to an alternative.